Lnformation of immigrants from the Sahaba to the second Abyssinia of Bani Amer (Journal of the College of Basic Education, 2022)
lslamic historical event is the migration of Muslims from Mecca to Abyssinia because of What they Were facing from hurting the leaders of Quraish to increase their number and show faith . The determin ation of Muslims to emigrate is their belief in God and obedience to What Allah ordered His Propher (peace and blessings of Allaah be uporn him ), And that the land of god is Wide protection for the lives of Muslims and fear for their religion and that immigration continues for everyone Who Wanted the face of God and feared himself injustice The Embodied tournaments companions of the in the steadfastness of the victory of lslam when they left the parentsand money for it.